Assessment of soil properties, plant yield and composition, after different type and applications mode of organic amendment in a vineyard of Mendoza, Argentina - Martínez, Laura Elizabeth (2018)
Research on grapevines has indicated that organic amendment application (OAA) increases the nutrient content of soil and plant tissue. Microbial functional groups are extensively used as soil fertility indicators because they are highly sensitive to changes in climatic and management conditions and they accurately represent entire biological processes. The goal of the present study was to evaluate the interactive effects of OAA on microbiological and chemical properties of soil and plants of a vineyard in Mendoza, Argentina. The following factors were evaluated: type of organic amendment (compost or vermi compost), application mode (surface or buried) and frequency of application (one or two applications). The field experiment was carried out using a factorial randomized complete block design. The following soil parameters were analyzed before and after OAA: microbial abundance related to the carbon and nitrogen cycle, total microbial activity, salinity and fertility. Yield, pruning weight, trunk diameter and nutritional variables of the vine were determined at the end of the assay. The results showed that microorganisms were not affected by the type of amendment, the application method or frequency. After OAA, the total abundance of microorganisms was similar, and soil salinity was not affected. Phosphorus depended on the strategy or combinations. Total phosphorus in petioles was higher after one or two buried applications (0.43% and 0.39%, respectively). In conclusion, OAA to irrigated soil of arid areas in Mendoza, Argentina, could be considered a promising supplementary treatment to increase the nutrient content in soil and vine.